The effectiveness of HRIS by using technology acceptance model on Human Resources Performances on Local Capability Development Department at Petronas Holding / Muhammad Firdaus Mohd Nasir - Mohd Nasir, Muhammad Firdaus (Faculty of Business and Management, 2013)
Nowadays, the elements in the Technology Acceptance Model have become essential to all organizations, especially when the organization recognized the important of HRIS in order to increase employee work performances. Therefore, this study is to carry out as an attempt to highlight the importance Technology Acceptance Model towards the Performances of Human Resources at the Local Capability Development Department, Petronas Holding. In order to identify the relationship between Technology Acceptance Model and Human Resources Performances, 60 sets of questionnaire has been distributed to the Local Capability Development Department, Petronas Holding. There are four elements in Technology Acceptance Model had been used which are Human Resources Process, Decision Making, Time and Cost Saving and Information Effect. Based on the research objectives and research questions that had been developed, the findings showed that the user of Technology Acceptance Model had been increased when the organization adapt all the elements into the working environment. Furthermore, based on the findings of correlation, it was found that all four elements in Technology Acceptance Model that has been used in this study have a positive relationship with Human Resources Performances. Therefore, the organization can provide better HRIS In the organization which can help the employees to Increase the efficiency In the workplace.